(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Promoting 24-hour healthy movement behaviours and wellbeing to reduce non-communicable diseases among adolescents is key to address population-level health challenges and health inequities. While interventions targeting young people are growing in number, implementation processes and outcomes often differ markedly between high- and low-income countries, particularly in participatory approaches. The Youth-Centred Participatory Action (YoPA, https://www.yopa-project.eu/) project aims to co-design and implement context-specific interventions in four diverse sites across Europe and Africa. Through participatory action research (PAR), adolescents and key stakeholders collaborate to co-create sustainable, community-embedded initiatives to improve movement behaviours and wellbeing, reducing non-communicable diseases. Despite growing interest in PAR approaches, evidence on how contextual barriers and facilitators influence their implementation, especially in global, multi-site settings, remains limited. This qualitative study provides a realist-informed process evaluation of Phase 1 of YoPA, focused on setting up local YoPA communities. It aims to identify challenges and facilitators during early implementation and to examine cross-site similarities and differences in initiating co-creation within varied socio-cultural and institutional contexts. Methods: Semi-structured interviews were conducted with 19 researchers, facilitators, and institutional stakeholders across all sites. Data sources included interview transcripts, facilitator logbooks, session plans, and local protocols. A qualitative thematic analysis was conducted using MAXQDA. Findings were interpreted using the ICAMO (Intervention–Context–Actors–Mechanisms–Outcomes) realist framework. Results: While barriers and facilitators varied strongly across contexts, some commonalities emerged. A key finding was the crucial role of the actors in implementation. Elements of the co-creation protocol, such as applying theoretical frameworks with youth and adapting content to local contexts, proved challenging. Additionally, communication barriers were noted, particularly in engaging adolescents meaningfully. Some mechanisms, like giving voice to youth and sharing power, were central. Facilitators included strong ties with local host institutions or agents (e.g. teachers, youth coordinators) and integrating action team sessions into existing activity curricula. Ultimately, despite a shared intervention approach, local context significantly shaped intervention characteristics. Conclusion: This study offers comparative insights on implementing co-creation in multi-country projects to promote youth wellbeing and movement. These insights can support researchers and practitioners in preparing and conducting PAR to co-create more effective, locally relevant interventions.